If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = -50 Solving 13 + -9x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -9x = -50 + -13 Combine like terms: 13 + -13 = 0 0 + -9x = -50 + -13 -9x = -50 + -13 Combine like terms: -50 + -13 = -63 -9x = -63 Divide each side by '-9'. x = 7 Simplifying x = 7
| y+3=-11 | | 12=7x+25 | | 12x+124=-32 | | 79=7x+12 | | 120-11x=-34 | | x+4-5x=3 | | 0.20s+0.32=520s | | (8y-7x)(8y+7x)= | | 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 | | 10-3t=4 | | 0.2b+9=0.5b+18 | | 3x*6=39 | | -2v(v-5)(v-6)=0 | | 7x(8-2)= | | 11k-5=9k+7 | | 11-46=n | | -3(4y-4)=2(1-7y)+11 | | 2ln(x)=21 | | 3k-5-10k=23-1k | | -2x-2=-6-2 | | 5+2(4x-3)= | | 3x(x+4)-4=2(x+4)+x | | 19.03-12.9h=-14h | | 4x-7-3+2x=8 | | -(3y-6)+4(5y-8)=8 | | -13y+7+9=-10y-11 | | 9(x+3)-5x-3(5+3x)= | | 0.5n-18=-4 | | -q+17=-2q | | 17c-9=18c-19 |